2016
DOI: 10.1039/c6py01261b
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-catalyzed controlled radical polymerization of N-vinylimidazole

Abstract: Laccase from Trametes versicolor catalyzes the controlled radical polymerization of N-vinylimidazole, yielding narrowly dispersed, metal-free polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 79 publications
0
43
0
Order By: Relevance
“…27,28 Moreover, surface-initiated enzymatic polymerizations of DNA by terminal deoxynucleotidyl transferase have been explored to amplify signals in biosensing. [29][30][31][32][33][34] Recently, we and others have shown that metalloproteins such as hemoglobin (Hb), horseradish peroxidase, and laccase can catalyze ATRP in solution [35][36][37][38][39][40][41][42] and on surfaces. 39,43,44 These biocatalysts represent a biocompatible, nontoxic and environmentally friendly alternative to conventional, transition metal-based ATRP catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Moreover, surface-initiated enzymatic polymerizations of DNA by terminal deoxynucleotidyl transferase have been explored to amplify signals in biosensing. [29][30][31][32][33][34] Recently, we and others have shown that metalloproteins such as hemoglobin (Hb), horseradish peroxidase, and laccase can catalyze ATRP in solution [35][36][37][38][39][40][41][42] and on surfaces. 39,43,44 These biocatalysts represent a biocompatible, nontoxic and environmentally friendly alternative to conventional, transition metal-based ATRP catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Among those is the conductive polymer polyaniline (PANI), the laccase-mediated synthesis of which was outlined in a recent review [149]. The atom transfer radical polymerization of N-vinylimidazole catalyzed by T. versicolor laccase showcased its ability to produce a polymer with a well-defined molecular mass and potential applications in drug and gene delivery, fuel cell membranes, and polyionic liquids [150]. Another laccase-mediated polymerization in a highly controlled manner produced alternating copolymers of catechol and xylylenediamines with potential applications as imaging agents [151].…”
Section: Plastics and Biopolymersmentioning
confidence: 99%
“…Yet, enzymatic catalysis works not only in vivo, but also for biological or even synthetic polymers in vitro . In the presence of a suitable substrate, some enzymes like horseradish peroxidase (HRP) or laccase produce radical species as byproducts, which can be utilized as environmentally friendly initiators for radical polymerizations . The mechanism of HRP‐mediated radical polymerization is well known, and also sketched in Figure .…”
Section: Introductionmentioning
confidence: 99%